2003
DOI: 10.1037/0022-006x.71.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse and Number of Sexual Partners in Young Women: The Role of Abuse Severity, Coping Style, and Sexual Functioning.

Abstract: The authors proposed and tested a model describing distinct pathways through which childhood sexual abuse (CSA) may lead to relatively low or high numbers of sexual partners in adulthood. Path analyses were conducted on survey responses of young female U.S. Navy recruits who reported CSA (N ϭ 547). Use of avoidant strategies to cope with CSA was expected to produce higher levels of sexual problems and fewer heterosexual sex partners, whereas use of self-destructive coping strategies was expected to result in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 66 publications
4
83
0
1
Order By: Relevance
“…However, other age cut-offs have also been reported, including age 17 (e.g., Paul, Catania, Pollack, & Stall, 2001;Walser & Kern, 1996) age 16 (e.g., Bartoi & Kinder, 1998;Kalichman, Gore-Felton, Benotsch, Cage, & Rompa, 2004), age 15 (e.g., Jinich et al, 1998;Mayall & Gold, 1995), age 14 (e.g., Merrill, Guimond, Thomsen, & Milner, 2003), and age 13 (e.g., Carballo-Dieguez & Dolezal, 1995;DiIorio, Hartwell, & Hansen, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…However, other age cut-offs have also been reported, including age 17 (e.g., Paul, Catania, Pollack, & Stall, 2001;Walser & Kern, 1996) age 16 (e.g., Bartoi & Kinder, 1998;Kalichman, Gore-Felton, Benotsch, Cage, & Rompa, 2004), age 15 (e.g., Jinich et al, 1998;Mayall & Gold, 1995), age 14 (e.g., Merrill, Guimond, Thomsen, & Milner, 2003), and age 13 (e.g., Carballo-Dieguez & Dolezal, 1995;DiIorio, Hartwell, & Hansen, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Research has shown that there are 2 responses to sexual abuse: one that reflects inhibition and the other that reflects excitation, and it is in the latter group that more sexual behavior is observed. 13 …”
Section: Definitionmentioning
confidence: 99%
“…A positive answer to any of these nine screening questions was followed with questions asking more detailed information regarding the nature of the CSA incident that included: 1) type of physical contact, 2) age of the participant at the time of the abuse, 3) frequency of abuse, and 4) relationship of the perpetrator to the participant. A multidimensional index of CSA capturing the severity of the abuse experience was created using the additional information that have been demonstrated to individually predict a variety of severe outcomes (11,12).…”
Section: Definitions Of Child and Adultmentioning
confidence: 99%
“…Higher scores on any of the dimensions of the CSA experience reflect greater levels of CSA severity (12,13,14).…”
Section: Definitions Of Child and Adultmentioning
confidence: 99%